The Relationship between Abilities and Album Coordination to the Abilities of Pencak Silat Sabit Kick - Idris Maulana Idris; Rudi Rudi; Indrayogi Indrayogi (Universitas Majalengka, 2023)
Mastery of pencak silat techniques is the most basic complement, without neglecting other elements such as physical, tactical and mental conditions. The purpose of this study was to determine the relationship between agility and ankle coordination on the ability of pencak silat kicks. This research method is a correlation research. In this study, the population consisted of 15 students participating in the pencak silat extracurricular activity. In this study, the sampling technique used for the extracurricular students at the Korpri Vocational High School was a total sampling of 15 students. Then the research instrument used an agility test and an ankle coordination test as well as a Sabit kick ability test. Based on the results of data analysis, description, testing of research results, and discussion, it can be concluded that there is a significant relationship between agility and sabit kick abilities of extracurricular Pencak Silat Students at Korpri Vocational School, with a value of rx1.y = 0.693 > r (0.05)(12) = 0.532. There is a significant relationship between ankle coordination and the sabit kick ability of students of the Pencak Silat extracurricular at Korpri Vocational School with a value of rx2.y = 0.866 > r (0.05)(12) = 0.532. There is a significant relationship between agility and ankle coordination on the ability to kick the Pencak Silat sabit kick at Korpri Vocational High School, with a value of Ry (x1.x2) = 0.911 > R (0.05)(12) = 0.532.